Respostas
respondido por:
0
x - 3y = 1 * (-1)
2x -y = 17
-x +3y = -1
2x - y = 17
x + 2y = 16
x = 16 - 2y
x - 3y = 1
(16 -2y) -3y = 1
16 -2y -3y = 1
-5y = 1 - 16
-5y = -15 * (-1)
5y = 15
y = 15/5
y = 3
x = 16 - 2y
x = 16 - 2*3
x = 16 -6
x = 10
2x -y = 17
-x +3y = -1
2x - y = 17
x + 2y = 16
x = 16 - 2y
x - 3y = 1
(16 -2y) -3y = 1
16 -2y -3y = 1
-5y = 1 - 16
-5y = -15 * (-1)
5y = 15
y = 15/5
y = 3
x = 16 - 2y
x = 16 - 2*3
x = 16 -6
x = 10
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás